“Taking our language back home” - Motivation and challenges in the South Sami area - Steinfjell, Risten Birje (UiT Norges arktiske universitet, 2014)
The South Sami language was the daily language of the South Sami before Norwegianisation and assimilation made it less used among the South Sami themselves and useless in the Norwegian society. The language was then not transmitted to the next generation anymore and UNESCO listed the language as severely endangered. The topic of this thesis is the revival that has taken place in the South Sami area for the last decade and which is still ongoing. As a result of this, the status of the South Sami language has changed and it is now equalized with Norwegian in two municipalities after they were incorporated into the Sami administrative language area. Institutions have been established to keep the culture and the language alive. My focus is the home as an arena for language revitalization. Many South Sami have after becoming parents made the South Sami language their home language, though Norwegian was their daily language when growing up. I look closer at what the motivation is for these parents and what kind of challenges regards to the language shift in making the children functionally bilingual. It is difficult to make the children functionally bilingual only by using the language at home. The Intergenerational language transmission is important, in connection that the language is in use in other domains. The future of the language is brighter because of the positive changes.